2017
DOI: 10.1590/1519-6984.09416
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the applicability of functional diversity in Biological Conservation

Abstract: Functional diversity is increasingly pointed as a useful approach to reach Biological Conservation goals. Here, we provide an overview of the functional diversity approach status in the Biological Conservation field. We sought for peer-reviewed papers published over a period of twenty years (from 1994 to 2014). First we used the general topic "functional diversity" and then refined our search using the key-word "conservation". We have identified the conservation strategies addressed, the organism studied, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 62 publications
(72 reference statements)
0
10
0
Order By: Relevance
“…Ecosystem functioning is linked with the functional diversity of the species within ecosystems [23]; therefore selecting the right species traits and metrics to estimate functional diversity has become a priority. A recent review [24] demonstrated that a plurality of functional diversity studies have been of plants (31%), while a far smaller proportion of studies have been of fishes (8%). Most of the latter studies focus on marine species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ecosystem functioning is linked with the functional diversity of the species within ecosystems [23]; therefore selecting the right species traits and metrics to estimate functional diversity has become a priority. A recent review [24] demonstrated that a plurality of functional diversity studies have been of plants (31%), while a far smaller proportion of studies have been of fishes (8%). Most of the latter studies focus on marine species.…”
Section: Introductionmentioning
confidence: 99%
“…However, fish were usually not Journal of Geographic Information System taken into account in these analyses. Freitas & Mantorani[24] reviewed the works published from 1994 to 2014 and found that only 8% of the 621 functional diversity studies are about fish. Likewise, only 8% of these studies were performed on a global scale.…”
mentioning
confidence: 99%
“…Analyzing scientific production in terms of environmental themes is recognized as an important conservation tool (Nabout et al 2012), producing a detailed understanding of different areas of knowledge (Teodoro et al 2020). In addition, it enables the identification of researchers' preferences for certain areas, study locations, definition of concepts and applications, main trends, and gaps regarding the themes considered (Kullenberg and Kasperowski 2016;Freitas and Mantovani 2018;Hannibal et al 2019;Baldiviezo et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…These ecological strategies can lead to inferences regarding the resilience potential of a fragmented area. Combining the measurements of functional attributes in facing the similarity of their ecological functions can clarify the role of the tree community (Freitas and Mantovani, 2017) through the set of plants with functional redundancy, meaning strategies of similar ecological conditions, in which the condition for them to be allocated in areas under anthropic disturbance is verifi ed (Pillar et al, 2013).…”
Section: Introductionmentioning
confidence: 99%